Biodegradation of polyhydroxyalkanoates: current state and future prospects - Paloyan, Ani; Tadevosyan, Mane; Ghevondyan, Diana; Khoyetsyan, Lev; Karapetyan, Mariam; Margaryan, Armine; Antranikian, Garabed; Panosyan, Hovik (Frontiers in Microbiology, 2025)
Polyhydroxyalkanoates (PHAs) are biobased and biodegradable polymers that offer a sustainable alternative to conventional plastics, addressing the escalating concerns over plastic pollution. While their environmental advantages are well-documented, the efficient degradation of PHAs in natural and engineered environments remains a critical component of their lifecycle. This review provides a comprehensive overview of PHA-degrading bacteria isolated from diverse ecosystems and highlights the pivotal role of PHA depolymerases in achieving PHA circularity. Microbial adaptation to diverse environmental conditions, such as extreme temperatures, salinity, and pH, significantly influences enzymes properties, including the stability, activity, and substrate specificity of PHA-degrading enzymes. These adaptations often enhance enzyme, performance, enabling functionality under challenging conditions. Consequently, extremophilic microorganisms are invaluable resources for discovering and engineering robust PHA depolymerases for industrial and environmental applications. This review underscores the urgent need for further research to improve the ecological and economic sustainability of PHA waste management.